2020
DOI: 10.1177/1535370220966963
|View full text |Cite
|
Sign up to set email alerts
|

Shortened derivatives from native antimicrobial peptide LyeTx I: In vitro and in vivo biological activity assessment

Abstract: In the continuing search for novel antibiotics, antimicrobial peptides are promising molecules, due to different mechanisms of action compared to classic antibiotics and to their selectivity for interaction with microorganism cells rather than with mammalian cells. Previously, our research group has isolated the antimicrobial peptide LyeTx I from the venom of the spider Lycosa erythrognatha. Here, we proposed to synthesize three novel shortened derivatives from LyeTx I (LyeTx I mn; LyeTx I mnΔK; LyeTx I mnΔKAc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, a study using artificial intelligence 100,000 peptides of which 200 were synthetized and tested; the results showed that a peptide shorter than usual, containing nine amino-acid residues, presented minimum inhibitory concentration (MIC) lower than 1 µM ( Cherkasov et al, 2009 ). Other studies using antimicrobial peptides derived from other animals also showed that shortened peptides produced better antimicrobial activity ( Solstad et al, 2020 ; Fuscaldi et al, 2021 ).…”
Section: Physicochemical Properties That Influence the Antimicrobial ...mentioning
confidence: 92%
“…Furthermore, a study using artificial intelligence 100,000 peptides of which 200 were synthetized and tested; the results showed that a peptide shorter than usual, containing nine amino-acid residues, presented minimum inhibitory concentration (MIC) lower than 1 µM ( Cherkasov et al, 2009 ). Other studies using antimicrobial peptides derived from other animals also showed that shortened peptides produced better antimicrobial activity ( Solstad et al, 2020 ; Fuscaldi et al, 2021 ).…”
Section: Physicochemical Properties That Influence the Antimicrobial ...mentioning
confidence: 92%
“…This strategy has been useful in synthesising short derivatives of proteins. For instance, it has been used to produce short portions of spider venom as potential AMPs 177,178 . It has also aided in examining the effect of AA substitution on the efficacy and stability of small AMPs 179,180 .…”
Section: Chemical Incorporation Of Ncaasmentioning
confidence: 99%
“…Nevertheless, the major problems of these conventional therapies were the relatively low success rate, serious side effects, and drug resistance [48][49][50]. Consequently, Lycotoxin I Lycosa carolinensis IWLTALKFLGKHAAKHLAKQQLSKL-NH 2 [24] Lycotoxin II Lycosa carolinensis KIKWFKTMKSIAKFIAKEQMKKHLGGE-OH [24] Lycocitin 1 Lycosa singoriensis GKLQAFLAKMKEIAAQTL-NH 2 [37] Lycocitin 2 Lycosa singoriensis GRLQAFLAKMKEIAAQTL-NH 2 [37] Ltc 1 Lachesana tarabaevi SMWSGMWRRKLKKLRNALKKKLKGE-OH [38] Ltc 2a Lachesana tarabaevi GLFGKLIKKFGRKAISYAVKKARGKH-OH [38] Ltc 3a Lachesana tarabaevi SWKSMAKKLKEYMEKLKQRA-NH 2 [38] Ltc 3b Lachesana tarabaevi SWASMAKKLKEYMEKLKQRA-NH 2 [38] Ltc 4a Lachesana tarabaevi GLKDKFKSMGEKLKQYIQTWKAKF-NH 2 [38] Ltc 4b Lachesana tarabaevi SLKDKVKSMGEKLKQYIQTWKAKF-NH 2 [38] Ltc 5 Lachesana tarabaevi GFFGKMKEYFKKFGASFKRRFANLKKRL-NH 2 [38] CIT 1a Lachesana tarabaevi GFFGNTWKKIKGKADKIMLKKAVKIMVKKEGISKEEAQAKVD AMSKKQIRLYLLKYYGKKALQKASEKL-OH [38] LyeTx I Lycosa erythrognatha IWLTALKFLGKNLGKHLAKQQLAKL-OH [39] Cupiennin 1a Cupiennius salei GFGALFKFLAKKVAKTVAKQAAKQGAKYVVNKQME-NH 2 [40] LyeTx I Lycosa erythrognatha IWLTALKFLGKNLGKHLAKQQLAKL-NH 2 [41] U1-SCRTX-Lg1a Loxosceles gaucho VGTDFSGNDDISDVQK-NH 2 [42] Lycotoxin-Pa4a Pardosa astrigera…”
Section: Anticancer Activitymentioning
confidence: 99%